Heterogeneously catalyzed energy release in azaborinine-based molecular solar thermal systems - Hussain, Zarah; Einholz, Ralf; Biebl, Sonja M.; Franz, Evanie; Müller, Adrian J.; Dreuw, Andreas; Bettinger, Holger; Brummel, Olaf; Libuda, Jörg (Topics in catalysis, 2025)
Molecular solar thermal (MOST) systems combine the conversion, storage and release of solar energy using switchable photoisomers. Isomerization of azaborinines (BN-benzenes) to their Dewar isomers (BN-Dewar) yields BNB/BND couples, representing a relatively new class of MOST systems with promising properties for energy storage. However, so far only homogeneous catalysts are available for triggering energy release, which does not allow for a straightforward catalyst-photoisomer separation. In this work, we investigate the heterogeneously catalyzed energy release of two different BNB/BND-based MOST systems, namely 1-(tert-butyldimethylsilyl)-2-mesityl-1,2-dihydro-1,2-azaborinine/2-(tert-butyldimethylsilyl)-3-mesityl-2-aza-3-borabicyclo[2.2.0]hex-5-ene (BNB1/BND1) and 1-(tert-butyl)-2-mesityl-1,2-dihydro-1,2-azaborinine/2-(tert-butyl)-3-mesityl-2-aza-3-borabicyclo[2.2.0]hex-5-ene (BNB2/BND2), using Au(111) as a potential catalytic material. We used highly oriented pyrolytic graphite (HOPG) as inert reference surface. In our study, we combined photochemical infrared reflection absorption spectroscopy (PC-IRRAS) with density functional theory (DFT). We show that Au(111) is active in releasing the energy stored in a BNB/BND MOST system. However, the catalytic activity is strongly dependent on the substituents. Although the activity of the Au catalyst is too low to be implemented in applications, our study provides proof of principle that a heterogeneously catalyzed approach is applicable.